Infective endocarditis, 1984 through 1993: a clinical and microbiological survey - Benn, M.; Hagelskjær, L. H.; Tvede, M. (Journal of internal medicine, 1997)
Benn M, Hagelskjær LH, Tvede M. (Viborg Hospital, Denmark). Infective endocarditis, 1984 through 1993: a clinical and microbiological survey. J Intern Med 1997; 242: 15–22. Objectives To characterize the epidemiology and the clinical and microbiological spectrum of infective endocarditis in a Danish population. Design A retrospective review. Setting All episodes hospitalized of infective endocarditis from 1984 to 1993 in Viborg County were reviewed. The county is served by one general and four local hospitals. Subjects One hundred and nine episodes of suspected infective endocarditis with 62 episodes in 59 patients fulfilling the diagnostic criteria by von Reyn. Results An overall incidence of 27 episodes per million per year was found. The incidence was 17.4 episodes per million per year in the first part of the decade and 36.5 episodes per million per year in the second part (P < 0.001). Microscopic haematuria was found in 70.2% of the patients with infective endocarditis, compared to 16.7% of the patients in whom the diagnosis was rejected (P < 0.01). Staphylococcus aureus was found in 38.9%, non‐β‐haemolytic streptococci in 24.1% and Enterococcus faecalis in 16.7%. The overall mortality was 35.5%. The mortality decreased significantly from 50.0% in the first part of the decade to 28.6% in the second part (P < 0.01). The mortality was 23.1% in patients in whom the diagnosis was established whilst they were alive. This finding was significantly lower than the overall mortality (P < 0.05). Conclusion The incidence of infective endocarditis increased during the decade. The frequency of non‐β‐haemolytic streptococci was lower than normally reported. Mortality is still high, with the main mortality within the first week in hospital, which stresses the importance of early case detection and treatment.